Arsitektur Kebijakan Halal yang Responsif: Membangun Ekonomi Digital Syariah Berbasis Blockchain dan E-Commerce yang Inklusif dan Kompetitif - Faizah, Siti Inayatul (Matan : Journal of Islam and Muslim Society, 2025)
The global halal industry is undergoing a significant transformation as Muslim and non-Muslim consumer preferences increase, strengthening the position of halal products as a strategy in the economic diplomacy of Muslim countries. This study examines the dynamics of the global halal industry focusing on the integration of Islamic values, sustainability, and technology. This research employs a qualitative method by utilizing a literature review as the basis for analyzing existing data. The concept of halalan thayyiban is positioned as a new standard that is more holistic than the conventional legal-formal approach, encompassing social justice, ecological balance, and community welfare. Furthermore, the concept of a Green Halal Economy is introduced as a synergy between Sharia principles, the green economy, and the Sustainable Development Goals (SDGs), supported by case studies from several countries. This study also discusses the urgency of digitalizing the halal system through technologies such as blockchain, AI, and IoT, while identifying policy gaps that hinder such integration. Recommendations are proposed for the reformulation of inclusive halal policies, adaptive to digitalization, and based on Islamic ecological values through cross-country and institutional collaboration. This study provides a conceptual contribution to the development of a sustainable and inclusive future halal ecosystem globally.